Joint‐sparing versus nonjoint‐sparing reconstruction of the radius following oncologic resection: A systematic review. Issue 8 (25th August 2021) - Lunn, Kiera; Hoftiezer, Yannick; Lans, Jonathan; van der Heijden, Brigitte; Chen, Neal; Lozano‐Calderón, Santiago A.
Abstract : Background and Objectives: Reconstructions of the distal radius are uncommon procedures. This systematic review compares joints‐sparing (JS) versus nonjoint‐sparing (NJS) reconstructions following oncologic resection of the distal radius. Methods: A search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Collected outcomes included patient‐reported outcome measures (PROMs), range of motion and grip strength, and complication and reoperation rates. Results: A total of 52 nonrandomized cohort studies ( n  = 715) were included. PROMs were comparable between the cohorts, while the range of flexion‐extension was greater in JS reconstructions (78.1° vs. 25.6°) and the range of pronation‐supination was greater in NJS reconstructions (133.6° vs. 109.8°). Relative grip strength was greater following JS reconstruction (65.0% vs. 56.4%). About one in sixteen of the JS reconstructions were eventually revised to an NJS construct. Conclusions: This systematic review demonstrates that JS reconstructive techniques can offer satisfying results in patients treated for oncologic distal radius defects. However, about 6% of JS reconstructions are eventually revised to a NJS construct. Further investigation is warranted to identify factors that affect or predict these findings, to aid in future in treatment selection and reduce the common need for reoperations following these procedures.